2004
DOI: 10.1002/acp.1045
|View full text |Cite
|
Sign up to set email alerts
|

Language and spatial cognition: comparing the roles of landmarks and street names in route instructions

Abstract: Two experiments were conducted to investigate the processes involved when people use spatial descriptions intended to assist navigation. More specifically, we compared the effectiveness of route directions in an urban environment based on references either to landmarks or to street names. In the first experiment, the participants learned route directions that referred either to landmarks or to streets named after landmarks (e.g. a hospital vs. 'Hospital Street'). Processing times were shorter for instructions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
3
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 39 publications
2
50
3
1
Order By: Relevance
“…Our aim is to compare the effectiveness of landmark-based instructions with relative direction (left/right/straight) instructions (and with combinations such as "Turn left towards the X"). Several studies have pointed out that landmarks play a special role in the communication of route directions [2,5,9,17,19,21,24]. However, direction givers do not always prefer to give a landmark-based instruction and by studying in situ route instructions given by people, we noted that this seems to depend on where the instruction is given.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Our aim is to compare the effectiveness of landmark-based instructions with relative direction (left/right/straight) instructions (and with combinations such as "Turn left towards the X"). Several studies have pointed out that landmarks play a special role in the communication of route directions [2,5,9,17,19,21,24]. However, direction givers do not always prefer to give a landmark-based instruction and by studying in situ route instructions given by people, we noted that this seems to depend on where the instruction is given.…”
Section: Introductionmentioning
confidence: 81%
“…In Daniel & Denis' study [24], about 14-20% of route directions did not include a landmark. In Rehrl's study [20], in which participants were giving directions in situ, while walking along the route, only 1-7.4% of the directions were instructions without a landmark.…”
Section: Comparing Different Types Of Instructionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical studies demonstrated that landmarks facilitate navigation and that people prefer to use landmarks over street names when giving route directions themselves [24]. A formal representation language for route elements called wayfinding choremes is proposed and extended with context-specific landmarks [10,12,19].…”
Section: Related Workmentioning
confidence: 99%